The influence of microbial community dynamics on anaerobic digestion efficiency and stability: A Review - Amekan, Yumechris (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
An essential component in sustainable energy development is the production of bioenergy from waste. The most successful bioenergy technology worldwide is anaerobic digestion (AD), which is a microbially-mediated process of organic feedstock conversion into energy-rich compounds (volatile fatty acids (VFA) and biogas) for renewable energy generation. AD is deployed in a range of situations including systems for on-farm energy recovery from animal and plant waste to the processing of food and municipal solid waste (with the additional benefit of land-fill reduction).Anaerobic digesters rely on a diverse microbial community working syntrophycally through a series of interrelated biochemical processes.Each stage in anaerobic digestion is carried out by different microbial groups. Thus, to optimise energy recovery from the AD process, the microbial community must have stable performance over time, balancing the various metabolic functions and taxonomic community composition in digesters. Complicating this balance, it has been found that the presence of ammonia, sulphate, and hydrogen sulphide in substantial concentrations often cause failure in the AD process. Thus, these substances cause adverse shifts in microbial community composition and/or inhibit bacterial growth, that influencing AD performance.Â Â©2020. CBIORE-IJRED. All rights reserved